2014
DOI: 10.1037/a0035084
|View full text |Cite
|
Sign up to set email alerts
|

A test of two brief measures of the dark triad: The dirty dozen and short dark triad.

Abstract: There has been a substantial increase in the simultaneous study of 3 related constructs--psychopathy, Machiavellianism, and narcissism--since being termed the dark triad (DT; Paulhus & Williams, 2002). Growing interest in the DT has led to the development of 2 short, efficient measures that reduce the number of items typically used from 124 to 12 (Dirty Dozen, or DD; Jonason & Webster, 2010) and 27 (Short Dark Triad, or SD3; Jones & Paulhus, in press), respectively. Using a community sample collected online (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
152
4
8

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(179 citation statements)
references
References 27 publications
15
152
4
8
Order By: Relevance
“…Previous research has found stronger convergent and incremental validity between the Short-D3 and the original measures of the Dark Triad, as compared to the Dirty Dozen (Jonason & Webster, 2010;Maples, Lamkin, & Miller, 2014). In the present study, the Dirty Dozen measure demonstrated weaker convergent validity with the original Dark Triad measures and Honesty-Humility.…”
Section: Measurement Issues With the Dark Triadcontrasting
confidence: 50%
See 1 more Smart Citation
“…Previous research has found stronger convergent and incremental validity between the Short-D3 and the original measures of the Dark Triad, as compared to the Dirty Dozen (Jonason & Webster, 2010;Maples, Lamkin, & Miller, 2014). In the present study, the Dirty Dozen measure demonstrated weaker convergent validity with the original Dark Triad measures and Honesty-Humility.…”
Section: Measurement Issues With the Dark Triadcontrasting
confidence: 50%
“…Previous work also found that links between the Dirty Dozen and other measures of personality are weaker than those found with the SRP-III (e.g., Jonason & McCain, 2012;Jonason & Luévano, 2013;Miller et al, 2012). The same criticism may be applied to the Short-D3, because its items are not reflective of a vulnerable narcissism component (Maples et al, 2014). This may be why larger differences in correlations were found between the Short-D3 and NPI-16 than with the Dirty Dozen and NPI-16.…”
Section: Measurement Issues With the Dark Triadmentioning
confidence: 77%
“…However, the second tool -the Dirty Dozen -is controversial. Although some researchers have found it to be useful (Jonason and Luévano 2013;Rauthmann, 2012), the instrument has been critiqued in several recent reports (Jones and Paulhus 2014;Lee et al 2013;Maples et al 2014;Miller et al 2012). The main limitation is the psychometric cost of using this short measure.…”
Section: Measures Of the Dark Three Constructsmentioning
confidence: 99%
“…Extensive psychometric testing has been conducted on the utility of the SD3. Maples, Lamkin, and Miller (2014) found the SD3 to have adequate discriminant and criterion validity, as well as stronger convergent and incremental validity, than comparative measures available (e.g. The Dirty Dozen; Jonason & Webster, 2010).…”
Section: The Short Dark Triad (Sd3)mentioning
confidence: 99%